A Case of Susac Syndrome - Cho, Han Joo; Kim, Chul Gu; Cho, Sung Won; Kim, Jong Woo (Korean journal of ophthalmology, 2013)
The purpose of this article is to report on the first known Korean case of Susac syndrome. An 18-year-old female came to our clinic reporting blurred vision of the left eye for 2 days. She also complained of decreased hearing with tinnitus of the right ear and mild headache. She was previously healthy and had no remarkable medical history. Best-corrected visual acuity was 20 / 50 in the left eye and 20 / 20 in the right eye. An axiomatic triad of ocular, cochlear, and neurologic involvement was observed in the patient. Fluorescein angiography showed branched retinal arterial occlusions in the left eye. A sudden right sensorineural hearing loss was observed on audimetry. Magnetic resonance images showed a hyperintense lesion in the white matter around the corpus callosum. The patient was treated with high doses of systemic corticosteroids, and no neuropsychological sequelae were observed. This is the first case report of Susac syndrome in Korea. In cases of retinal arterial occlusion with hearing loss or neuropsychological symptoms, Susac syndrome should be suspected.